PRELIMINARY OBSERVATIONS ON THE TRANSMISSION OF VIRUSES WITH Peregrinus maidisl - VARÓN DE AGUDELO, FRANCIA; MARTÍNEZ-LÓPEZ, GERARDO (Revista Colombiana de Entomología, 1980)
Studies on the identification of insect vectors of complex symptoms caused by a virus in corn (Lea mays L.) showed that Peregrinus maidis (Asmead) (Homoptera: Delphacidae) was prevalent within insect populations from affected cornfields in the Cauca Valley (Colombia). Preliminary observations were done on insect habits and inoculations of corn seedlings using groups of insects collected from cornfields. The results suggested that P. maidis is transmitting at least three or four different viruses according to differences in symptomatology and electron microscopy observations. One of them is similar to Maize Mosaic Virus (MMV); a rhabdovirus with different serological reactions to MMV; a third similar in shape and size to "Maize Hoja Blanca Virus" and the last similar in shape but the different serological reaction to maize _.stripe Virus of U.S.A.